Design and Analysis of Application of CVT (Continously Variable transmition) On Activator Washing Machine Mechanic Maximum Capacity 7kg - Oscar Haris; Zaenudin; Agus Darmawan; Yosa; Komin (Nusa Putra University, 2020)
Washing clothes is an important activity in everyday life, but it requires time, effort and money. Currently there are many washing machines manufactured by products on the market with one-tube and two-tube types that use electrical energy and digital modules as their operating tools. In this study, the application of CVT (Continuously Variable Transmition) in Mechanical Drive Washing Machines is designed, which utilizes human power as a resource so that it can reduce the use of electrical energy and can save costs besides that it can also be a means of exercise. The washing machine tube rotation is generated from the pedal stroke, which is passed from the sprocket or chain ring to the CVT which then goes to the pinion gear as changing the axial CVT rotation position to radial to rotate the washing tube.